Survive the Dome - Jackson, Kosoko (Naperville, Illinois : Sourcebooks Fire, 2022)
"A high school junior teams up with a hacker during a police brutality protest to shut down a device that creates an impenetrable dome around Baltimore that is keeping the residents in and information from going out"--.
Ages 14.
Grades 10-12.
Keywords: Protest movements -- Fiction; Hacking -- Fiction; Race relations -- Fiction; Police -- Fiction; African Americans -- Fiction; Hispanic Americans -- Fiction; Gay people -- Fiction; Baltimore (Md.) -- Fiction; Novels; Science fiction